A branch-and-bound approach to schedule a no-wait flow shop to minimize the CVaR of the residual work content. (March 2019) - Urgo, M.
Highlights: A flow shop stochastic scheduling approach minimizing the CVaR of the residual work content. A robust schedule is devised to cope with the uncertain availability of workforce. Good performance in comparison with the scheduling approaches used in the company. Solution times are compatible with the dimension of aggregate scheduling problems. Abstract: The aerospace industry ranks among the largest manufacturing industries in the world facing a significant growing phase as well as an increased competition. This paper addresses the scheduling of a set of jobs in a paced assembly line in presence of uncertainty affecting the availability of production resources, stemming from the assembly process in the aircraft manufacturing industry. The production problem is modeled as a no-wait paced permutation flow shop and solved providing a robust scheduling solution minimizing the conditional value-at-risk ( CVaR ) of the residual work content, i.e., the amount of workload that cannot be completed during the cycle time in the stations, due to a lack of available resources. A branch-and-bound approach is developed and applied to randomly generated instances as well as to an industrial problem related to the production of aircrafts.